2004
DOI: 10.1042/bj20031762
|View full text |Cite
|
Sign up to set email alerts
|

The active site and substrate-binding mode of 1-aminocyclopropane-1-carboxylate oxidase determined by site-directed mutagenesis and comparative modelling studies

Abstract: The active site and substrate-binding mode of MD-ACO1 (Malus domestica Borkh. 1-aminocyclopropane-1-carboxylate oxidase) have been determined using site-directed mutagenesis and comparative modelling methods. The MD-ACO1 protein folds into a compact jelly-roll motif comprised of eight a-helices, 12 b-strands and several long loops. The active site is well defined as a wide cleft near the C-terminus. The co-substrate ascorbate is located in cofactor Fe2+-binding pocket, the so-called '2-His-1-carboxylate facial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 31 publications
(43 reference statements)
1
26
1
Order By: Relevance
“…1b; numbering of amino acid positions according to spruce ACO) and is believed to interact by strong charge-charge interactions (Seo et al 2004;Zhang et al 2004). The RXS motif is another common region of the family and binds 2-oxoglutarate (Roach et al 1995), but has been modeled by Seo et al (2004) to bind ascorbate in ACO (Arg-258-X-Ser-260; Fig. 1b).…”
Section: Sequence Relatedness Of Conifer and Angiosperm Aco Proteinsmentioning
confidence: 97%
See 2 more Smart Citations
“…1b; numbering of amino acid positions according to spruce ACO) and is believed to interact by strong charge-charge interactions (Seo et al 2004;Zhang et al 2004). The RXS motif is another common region of the family and binds 2-oxoglutarate (Roach et al 1995), but has been modeled by Seo et al (2004) to bind ascorbate in ACO (Arg-258-X-Ser-260; Fig. 1b).…”
Section: Sequence Relatedness Of Conifer and Angiosperm Aco Proteinsmentioning
confidence: 97%
“…For further structural comparison of conifer and angiosperm ACOs, we modeled the spruce and Douglas Wr ACO proteins with ACO from petunia, for which a crystal structure is available (Zhang et al 2004), and ACO from apple, which has previously been modeled on the crystal structure of a related isopenicillin-N-synthase (Seo et al 2004) and structurally characterized (Rocklin et al 1999;Zhou et al 2002;Tierney et al 2005) (Fig. 1b).…”
Section: Sequence Relatedness Of Conifer and Angiosperm Aco Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…The rooting was based on midpoint. Molecular phylogenetic analysis of the 13 Arabidopsis ACO and the three Lepidium ACO sequences was achieved by comparison of the amino acid sequence of the iron binding conserved domain, which is specific for the 2OG-Fe(II) oxygenase family (see Supplemental Figure 3 and Supplemental Data Set 9 online; Seo et al, 2004).…”
Section: Sequence Alignments and Molecular Phylogenetic Analysismentioning
confidence: 99%
“…The obtained model was energy minimized by macro model module from Schrodinger and is evaluated for its quality. To evaluate the stereochemical quality of the minimized structure, PROCHECK [51] software was utilized in the study which showed the superiority of the optimized model over the initial model with an appreciable distribution of ψ and ϕ angels in Ramachandran plot. With the Sitemap module of Schrodinger, the active site of the receptor was identified [33].…”
Section: Homology Modeling Of Human 5-ht 2c Receptor and Docking Studiesmentioning
confidence: 99%